2012
DOI: 10.30536/j.ijreses.2012.v9.a1823
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Vegetation Indices to Detect the Tropical Rain Forest Changes Using Breaks for Additive Seasonal and Trend (Bfast) Model

Abstract: Remotely  sensed  vegetation  indices  (VI)  such  as  the  Normalized  Difference Vegetation Index (NDVI) are increasingly used as a proxy indicator of the state and condition of  the  land  cover/vegetation,  including  forest.  However,  the  Enhanced  Vegetation  Index (EVI)  on  the  outcome  of  forest  change  detection  has  not  been  widely  investigated.  We compared the influence of using EVI and NDVI on the number and time of detected changes by applying Breaks for Additive Seasonal and Trend (BFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Different vegetation types respond differently to groundwater presence in aquifers [33]. NDVI is a conventional vegetation index, but recent studies suggest that the EVI, with a more robust profile in areas with atmospheric disturbance, can be derived from Landsat 8-9 data [34]. Equation ( 2) outlines the general formula for determining the EVI, covering the canopy background with the L value.…”
Section: Groundwater Availability (Ga)mentioning
confidence: 99%
“…Different vegetation types respond differently to groundwater presence in aquifers [33]. NDVI is a conventional vegetation index, but recent studies suggest that the EVI, with a more robust profile in areas with atmospheric disturbance, can be derived from Landsat 8-9 data [34]. Equation ( 2) outlines the general formula for determining the EVI, covering the canopy background with the L value.…”
Section: Groundwater Availability (Ga)mentioning
confidence: 99%
“…On a global scale, the NDFI spectral index has been used to detect changes in the structure of tropical forests and detect degradation patterns, either with Landsat or MODIS images [5,6,7]. In Latin America, it has been used in investigations to monitor forest degradation and deforestation, mainly in the Brazilian Amazon, and to detect selective extraction activities in areas with forest management plans.…”
Section: Introductionmentioning
confidence: 99%
“…BFAST decomposes into the time series trend, seasonal, and remainder components. BFAST was widely used to study vegetation changes in different parts of the world for various applications [32][33][34][35][36][37][38][39]. The comparison of BFAST, MRA-WT, and STL by [23] showed that BFAST was the most accurate approach for their dataset.…”
Section: Introductionmentioning
confidence: 99%